Analysis of Ease of Use as a Moderating Variable in Factors Influencing Behavioral Intention to Use Green Product Innovation - Intan Mahalayati (PT SOLUSI EDUKASI BERDIKARI, 2026)
This study examines the factors influencing consumer behavioral intention to adopt green products, focusing on the moderating role of perceived ease of use. Using a sample of 300 respondents, the research analyzes the effects of perceived relative advantage, compatibility, complexity, trialability, observability, and ease of use on behavioral intention to adopt Philips MyCare LED bulbs. Data analysis was conducted using multiple linear regression and moderation testing in SPSS. Results indicate that all factors positively influence behavioral intention, and perceived ease of use strengthens the relationships between the independent variables and behavioral intention. The model explains 66% of behavioral intention variance, suggesting strong predictive power. The findings offer theoretical contributions to green innovation adoption literature and practical guidance for companies developing environmentally friendly products, emphasizing ease of use, compatibility, and perceived benefits to encourage consumer adoption.